The origins of fairness : how evolution explains our moral nature - Baumard, N. (Nicolas) (Foundations of human interaction., 2016)
Develops further John Rawls' intuition that our sense of justice is rooted in our evolutionary past and presents a new theory of morality based on evolutionary biology.